Isolation and Screening of Cellulolytic Bacteria from Yak (Bos grunniens) Excreta from Lahaul Valley Region for Pre-treatment of Paddy Straw in Himachal Pradesh - Kumar, Rajinder; Vatsa, Dinesh Kumar (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted during August, 2021 at Department of Agricultural Engineering, College of Agriculture, CSK Himachal Pradesh Krishi Vishvavidyalaya, Palampur to isolate and identify the cellulolytic bacteria from yak dung, yak dung manure and soil samples from spiti region in Lahaul-Spiti district of Himachal Pradesh. The bacterial isolates were identified by using morphological and biochemical standard methods, and identification based on Bergey’s Manual of Determinative Bacteriology. Cellulolytic bacteria from mentioned samples were isolated and cultured on CMC (Carboxymethyl cellulose) agar medium. The activity of cellulolytic bacterial was conducted based on halo area and cellulolytic index on CMC agar medium. Among 24 isolates of bacteria, 08 isolates were identified as cellulolytic bacteria. Furthermore, our isolates with higher cellulolytic index were identified as the Bacillus and Pseudomonas genus. Out of eight efficient cellulolytic isolates were identified as Bacillus spp. (06) three from yak dung manure, two from yak dung and one from soil sample and Pseudomonas spp. (02) one from yak dung manure and one from soil sample. Most Efficient cellulose degrading isolates of Bacillus spp. and Pseudomonas spp. were employed for biological pretreatment of paddy straw for two weeks and then run in laboratory biogas digester along with control digester. These digester sets were under observation from the second day of run upto three weeks and it was observed that the there was 10% hike in biogas production as compare to control digester on 22nd days at laboratory condition.